Enhance TL response due to radiation defects in Ge doped silica preforms - Ahmad Shaharuddin, Siti Shafiqah; Mohd Amin, Yusoff; Md. Nor, Roslan; Tamchek, Nizam; D.A, Bradley (Elsevier Limited, 2015)
Study has been made of the thermoluminescence (TL) response of Ge-doped silica preforms fabricated using the MCVD process and subsequently subjected to γ-ray irradiation. Two types of preform were fabricated, obtained using a different flow rate and deposition temperature for each case. Results from the absorption spectra of the samples show a signature absorption peak at 5.1 eV and 6.8 eV, indicative of oxygen-deficient and oxygen-rich defects respectively. The TL efficiency for both Ge samples were compared with the standard phosphor-based (LiF) thermoluminescence dosimeter, TLD100. For both sample types, a linear response has been obtained over the dose range 1–10 Gy. Analysis further showed the oxygen deficient Ge-doped silica sample provides a very much greater TL yield than TLD100, at 890 nC/Gy compared to 220 nC/Gy. Conversely, the oxygen rich sample gave a more limited response, with a sensitivity of 75 nC/Gy.